Optimasi Penggunaan Android Sebagai Peluang Usaha Di Masa Pandemik COVID’19 - Seta Samsiana; Rahmadya Trias Handayanto; Anita Setyowati Srie Gunarti; Irwan Raharja; Fata Nidaul Khasanah; Herlawati Herlawati; Maimunah Maimunah; Benrahman Benrahman (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2020)
Some community service activities have been done as a tangible form in building a resilient community in the current Covid '19 pandemic situation. Indonesia at the moment, from the various sectors of life, experienced the bad impact caused by this pandemic, especially in the economic sector. The current community service activity has three objectives: general, specific, and sustainable objectives. It has been carried out to accelerate the growth of entrepreneurial-skill and independent communities to fight against Covid'19 disaster. Housewives, in particular, the committee members of Islamic elementary school (SDIT) Prestasi Cendikia in Bekasi became our target community. The implementation process was as follows. 1) Participant registration through the Webinar. 2) Implementation of the activity through an online meeting with Google Meet, which was divided into two sessions, i.e. the first session of theoretical material such as Android functions, means of promotion, and managing the risk of failure; the importance of mastery of Android as a social medium of sales was explained. In addition, some technical application sessions were demonstrated directly in making the sales on the android app, i.e. shoope, selly and canva. 3) The evaluation where each participant filled a response about the implementation of this community service both training and workshop. The results of the questioner were presented through menti.com site that can be seen directly the values or graphs based on the participants' responses. The results showed that the participants demonstrated their creativity and were able to utilize Android as well as social media to sell products (services and goods). Keywords: Community Service, Android, SDIT Prestasi Cendikia. Abstrak Kegiatan pengabdian kepada masyarakat ini muncul sebagai wujud nyata membangun masyarakat tangguh di era pandemik Covid’19. Dimana Indonesia saat ini, dari berbagi sektor kehidupan mengalami kepurukan dihantam habis dampak pandemik, terlebih pada sektor ekonomi. Kegiatan ini mempunyai tiga tujuan, tujuan secara umum, khusus dan berkepanjangan. Kegiatan ini dilakukan untuk percepatan proses pertumbuhan kewirausahaan masyarakat mandiri dalam suasana Covid’19. Ibu-ibu rumah tangga khususnya anggota komite sekolah SDIT Prestasi Cendikia Bekasi menjadi masyarakat bidikan pengabdian kami. Metode pelaksanaan diawali dengan (1) Registrasi peserta melalui google form, Tahap (2) Pelaksanaan kegiatan melalui google meet, dengan materi seperti fungsi Android, sarana promosi, managemen dan resiko kegagalan, serta penjelaskan akan pentingnya penguasaan Android sebagai meda social penjualan. Tahap (3) Evaluasi: setiap peserta mengisi respon atau tanggapan terhadap pelaksanaan workshop pengabdian masyarakat ini. Hasil dari kuesioner melalui menti.com akan terlihat langsung nilai ataupun grafik tanggapan peserta pelatihan. Respon yang diperoleh kegiatan workshop bagus dan perlu dilanjutkan untuk masa-masa berikutnya. Hasil pelatihan ini peserta mampu melatih kreatifitas, membangun semangat memulai bisnis online dengan memanfaatkan penggunaan Android sebagai media sosial penjualan produk-produk baik jasa maupun barang. Kata Kunci: Pengabdian Masyarakat, Android, SDIT Prestasi Cendikia.